2009
DOI: 10.1007/s10571-009-9475-2
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulated GABAergic Expression in the Olfactory Bulb Layers of the Mouse Deficient in Monoamine Oxidase B and Administered With Amphetamine

Abstract: This study explores primarily the role of the activity of monoamine oxidase B (MAOB) in the regulation of glutamic acid decarboxylase 67 (GAD 67 ) expression in distinct layers of main olfactory bulb (OlfB), which links the limbic system. Moreover, the response of GAD 67 was investigated to amphetamine perturbation in the absence of MAOB activity. Immunocytochemical analysis was performed on OlfB sections prepared from the adult wild type (WT) and the MAOB gene-knockout (KO) mice after receiving repeated intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…This mechanism might explain the increased GAD67 expression as the bioinformatic analysis revealed several CRE elements in the promoter region upstream of the GAD67 transcription start site. Our data supported a direct relationship between CREB and GAD, as recently showed by Yin et al (2009), who reported that decreased phosphorylation of CREB is responsible for amphetamine-induced inhibition of GAD67 expression in the olfactory bulb. However, we cannot disregard the evidence of Murphy and Segal (2000) who demonstrated an indirect correlation between CREB phospholylation and GAD expression.…”
Section: Discussionsupporting
confidence: 92%
“…This mechanism might explain the increased GAD67 expression as the bioinformatic analysis revealed several CRE elements in the promoter region upstream of the GAD67 transcription start site. Our data supported a direct relationship between CREB and GAD, as recently showed by Yin et al (2009), who reported that decreased phosphorylation of CREB is responsible for amphetamine-induced inhibition of GAD67 expression in the olfactory bulb. However, we cannot disregard the evidence of Murphy and Segal (2000) who demonstrated an indirect correlation between CREB phospholylation and GAD expression.…”
Section: Discussionsupporting
confidence: 92%
“…The establishment and modulation of GABAergic inhibitory neuronal circuits in the CNS of rodents may be aided by BDNF-TrkB signaling [ 22 , 48 50 ]. Using the signaling of Ras/ERK (one of the TrkB signaling cascades), BDNF/TrkB can potentially stimulate p-CREB activation of the GAD-65 promoter (5.5-kb 5' GAD65-luc construct) and regulatory zones in cortical inhibitory interneurons, and the level of GAD-67 might be mediated through p-CREB within olfactory bulb cells [ 48 , 51 ]. Furthermore, via modulating the PLC-1 and Shc cascade after SCI, BDNF-TrkB signaling can upregulate KCC2 expression, reducing spasticity and neuropathic pain [ 20 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…38,50 Sa´nchez-Huertas et al 40 found that BDNF/ TrkB could promote p-CREB activating of the GAD65 promoter (5.5-kb 5' GAD65-luc construct) and regulatory regions through Ras/ERK signaling (one of the TrkB signaling cascades) in cortical inhibitory interneurons. Yin et al 51 found that the GAD-67 level may be regulated by p-CREB in olfactory bulb cells. However, the mechanism of the p-CREB promoting the GAD-67 synthesis needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…Yin et al. 51 found that the GAD-67 level may be regulated by p-CREB in olfactory bulb cells. However, the mechanism of the p-CREB promoting the GAD-67 synthesis needs further study.…”
Section: Discussionmentioning
confidence: 99%